Community Social Capital and Early Childhood Social–Emotional Development: The Mediation of Parental Mental Health and the Moderation of Community‐Based Parenting Support Programs. - Zhao, Xiaotong; Zhang, Jiayu; Ma, Gaoming; Wu, Xiaogang (Child & Family Social Work, 2026)
This study investigates how community social capital shapes early childhood social–emotional development, with a particular focus on the mediating role of parental mental health and the moderating influence of community‐based parenting support programs. Drawing on data from the Survey on Early Education, Development and Strength (SEEDS) conducted in Hangzhou, China, we applied structural equation modelling and causal mediation analysis to uncover complex interrelationships among latent variables. The results demonstrate that community social capital exerts a significant positive impact on early childhood social–emotional development, mediated by improvements in parental mental health. Significantly, our findings demonstrate that community‐based parenting support programs act as a vital compensatory mechanism in communities with deficient social capital, offering essential resources and strengthening family resilience. These insights emphasise the need for policymakers to integrate parenting support programs into child‐friendly community frameworks, addressing disparities in social capital while fostering equitable developmental opportunities for children. By bridging gaps in community resources, such initiatives can play a transformative role in mitigating the adverse effects of resource‐poor environments on child development.